Diversity of Mollusks in The Intertidal Zone at Bahowo Beach, Manado, North Sulawesi - Rotinsulu, Prasuci; Maabuat, Pience; Romenda, Ardiawan; Papu, Adelfia (Masyarakat Moluska Indonesia, 2025)
The intertidal zone is a crucial habitat for various marine organisms, including Mollusca. Mollusca serve as bioindicators for assessing water quality. However, data on mollusc diversity in the coastal area of Bahowo Beach is still limited. Therefore, this study aimed to improve the knowledge of Mollusca diversity in this region. Molluscs were collected using 1×1 m plots placed randomly along vertical stratification. The samples were preserved in 70% alcohol and transported to the laboratory for identification using an identification guidebook. The assigned Mollusca were then analysed using Paleontological Statistics (PAST) software. The study recorded 79 individuals representing 41 species from two classes: Gastropoda and Bivalvia. The order Neogastropoda was the most dominant, with 22 species. The most abundant species was Littoraria scabra, with 16 individuals. The diversity index (H' = 3.209) falls into the high category, indicating that the Bahowo Beach ecosystem remains in good condition and continues to support mollusc life. Zona pasang surut merupakan habitat penting bagi berbagai biota laut, termasuk Mollusca. Mollusca berperan sebagai bioindikator untuk menilai kualitas lingkungan perairan tersebut. Data mengenai keanekaragaman Mollusca di wilayah pesisir Pantai Bahowo masih terbatas, sehingga dilakukanlah penelitian ini untuk menambah informasi mengenai keanekaragaman jenis Mollusca. Pengambilan Mollusca dilakukan dengan menggunakan plot 1×1 m secara acak, sampel yang diperoleh dimasukkan ke dalam plastik berisi alkohol 70% kemudian dibawa ke laboratorium untuk diidentifikasi menggunakan buku identifikasi. Mollusca yang telah diidentifikasi akan dianalisis menggunakan perangkat lunak Paleontological Statistics (PAST). Hasil Penelitian ini ditemukan 79 individu dari 41 spesies dari 2 kelas yaitu Gastropoda dan Bivalvia, dengan dominasi ordo Neogastropoda (22 spesies). Spesies terbanyak adalah Littoraria scabra (16 individu). Indeks keanekaragaman (H' = 3.209) menunjukkan kategori tinggi, yang menandakan ekosistem Pantai Bahowo masih dalam kondisi baik dan mendukung kehidupan Mollusca.